Combinatory local ablation and immunotherapies for hepatocellular carcinoma: Rationale, efficacy, and perspective - Chen, Shuling; Zeng, Xuezhen; Su, Tianhong; Xiao, Han; Lin, Manxia; Peng, Zhenwei; Peng, Sui; Kuang, Ming (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is the leading cause of cancer-related death worldwide. Local ablation, such as radiofrequency ablation, microwave ablation, cryoablation and irreversible electroporation, etc., are well established in elimination and control of HCC. However, high recurrence rate after local ablation remains the biggest challenge for HCC management. Novel and effective therapeutic strategies to improve long-term survival are urgently needed. Accumulating studies have reported the role of ablation in modulating the tumor signaling pathway and the immune microenvironment to both eliminate residual/metastatic tumor and promote tumor progression. Ablation has been shown to elicit tumor-specific immune responses by inducing massive cell death and releasing tumor antigen. Immunotherapies that unleash the immune system have the potential to enhance the anti-tumor immunity induced by ablation. Multiple combinatory strategies have been explored in preclinical and clinical studies. In this review, we comprehensively summarize the latest progress on different mechanisms underlying the effects of ablation on tumor cells and tumor microenvironment. We further analyze the clinical trials testing the combination of ablation and immunotherapies, and discuss the possible role of immunomodulation to boost the anti-tumor effects of ablation and prevent HCC recurrence.